An Experience Report of Remote Teaching about the IT Leadership Course - A Practical Approach - Rocha, Marina da S.; Dias, Gabriela A.; Oliveira, Gilberto; Sousa, Jorge Luiz; Andrade, Mateus; Rabelo, Jacilane de H. (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP), 2023)
Universities and extension projects had to redesign their teaching approaches and methods as a consequence to the replacement of face-to-face teaching by distance learning. The project LearningLab presents a proposal for a practical laboratory that offers courses to students in order to promote and expand their knowledge. This paper reports the findings of the application of the mentioned methodology on the course ‘Leadership in IT: A Practical Approach’. For this, examples of real situations from daily life in the labor market were used. The data obtained were analyzed qualitatively using the grounded theory method and quantitatively to identify positive and negative points related to the implementation of the course. The results show that the main positive points mentioned by the students were (a) the content covered in the course, (b) the teaching methodology, (c) examples of real situations, and (d) the didactics of the lecturers. 100% of the students pointed out that: (i) the teaching methodology was easy to learn, (ii) the content was easy to remember, (iii) the teaching was objective and clear, and (iv) questions were answered promptly. All the participants also did not find it tedious to submit the final project of the course. Therefore, the main contribution of this study can be noted on the student’s professional development of project LearningLab.